Morinda citrifolia L. leaf extract prevent weight gain in Sprague-Dawley rats fed a high fat diet - Jambocus, Najla Gooda Sahib; Ismail, Amin; Khatib, Alfi; Mahomoodally, Fawzi; Saari, Nazamid; Mumtaz, Muhammad Waseem; Abdul Hamid, Azizah Abdul (Taylor and Francis Ltd., 2017)
Background: Morinda citrifolia L. is widely used as a folk medicinal food plant to manage a panoply of diseases, though no concrete reports on its potential anti-obesity activity. This study aimed to evaluate the potential of M. citrifolia leaf extracts (MLE60) in the prevention of weight gain in vivo and establish its phytochemical profile.